Evaluation of PC‐ISO for customized, 3D printed, gynecologic 192Ir HDR brachytherapy applicators. (8th January 2015) - Cunha, J. Adam M.; Mellis, Katherine; Sethi, Rajni; Siauw, Timmy; Sudhyadhom, Atchar; Garg, Animesh; Goldberg, Ken; Hsu, I‐Chow; Pouliot, Jean
Abstract : The purpose of this study was to evaluate the radiation attenuation properties of PC‐ISO, a commercially available, biocompatible, sterilizable 3D printing material, and its suitability for customized, single‐use gynecologic (GYN) brachytherapy applicators that have the potential for accurate guiding of seeds through linear and curved internal channels. A custom radiochromic film dosimetry apparatus was 3D‐printed in PC‐ISO with a single catheter channel and a slit to hold a film segment. The apparatus was designed specifically to test geometry pertinent for use of this material in a clinical setting. A brachytherapy dose plan was computed to deliver a cylindrical dose distribution to the film. The dose plan used an 192 Ir source and was normalized to 1500 cGy at 1 cm from the channel. The material was evaluated by comparing the film exposure to an identical test done in water. The Hounsfield unit (HU) distributions were computed from a CT scan of the apparatus and compared to the HU distribution of water and the HU distribution of a commercial GYN cylinder applicator. The dose depth curve of PC‐ISO as measured by the radiochromic film was within 1% of water between 1 cm and 6 cm from the channel. The mean HU was ‐ 10 for PC‐ISO and ‐ 1 for water. As expected, the honeycombed structure of the PC‐ISO 3D printing process created a moderate spread of HU values, but the mean was comparable to water. PC‐ISO is sufficiently water‐equivalent to be compatible with our HDR brachytherapy planning system and clinical workflow and, therefore, it is suitable for creating custom GYN brachytherapy applicators. Our current clinical practice includes the use of custom GYN applicators made of commercially available PC‐ISO when doing so can improve the patient's treatment. PACS number: none